CO2 corrosion resistant self-repairing intelligent material as well as preparation method and application thereof
By developing a self-repairing intelligent material with a core-shell structure to resist CO2 corrosion, the problems of annular air traversing and wellbore integrity damage caused by cement ring corrosion under CCUS conditions are solved, and the anti-CO2 corrosion effect with fast response, high strength and fast self-repair are achieved, ensuring the safe storage and oil discharging efficiency of CO2.
Patent Information
- Application Number
- CN202311319664.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-12
- Publication Date
- 2025-04-15
AI Technical Summary
The corrosion of cement rings of the well under CCUS conditions is damaged due to the damage to the integrity of the annular air traversing and wellbore due to the corrosion of the cement ring of the well under CCUS conditions, and it is difficult to effectively repair the existing technology.
It provides a self-healing intelligent material that has a core-shell structure, the core layer contains formaldehyde-urea prepolymer and crotonic acid, and the shell layer contains acrylate monomers and cyclohexanollam, which is prepared by emulsion polymerization to impart CO2 response repair characteristics to the material.
In CO2 environment, it has a fast response speed, high strength of the responder, fast self-repair speed, and good corrosion resistance. It can effectively repair micro-cracks and micro-angle gaps of cement rings, ensuring safe storage and efficient oil discharging efficiency of CO2.
Smart Images

Figure BDA0004490550290000121
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of oil and gas exploration and development cementing engineering, and specifically relates to a CO2 corrosion resistant self-repairing intelligent material and a preparation method and application thereof. Background Art
[0002] The carbon capture, utilization and storage (CCUS) industry has bid farewell to the past demonstration project stage. As a powerful tool for achieving green and low-carbon development, CCUS has become one of the key technologies that are indispensable for the global goal of carbon neutrality. CCUS is a win-win feasible technical measure that can achieve CO2 geological storage and efficient oil recovery, but due to the influence of long-term high-pressure CO2 gas injection process and acidic CO2 gas, the cement ring and casing of CO2 injection wells and production wells suffer serious corrosion damage. After long-term CO2 corrosion damage, the mechanical properties of the cement ring have greatly declined, and corrosion microcracks and micro-annuli have occurred in the cement ring matrix, the first interface and the second interface, causing air channeling and integrity damage to the wellbore annulus, seriously affecting the CO2 storage and oil recovery efficiency.
[0003] Conventional remedial measures such as cement and resin are usually used to address the problems of air leakage and damaged integrity of the wellbore annulus. Conventional cement slurry systems and micro / ultrafine cement slurry systems cannot effectively squeeze into narrow gaps and achieve effective repairs for corroded microcracks and microannuli. The resin system can achieve narrow gap plugging and repair due to its low viscosity and strong injectability, but due to its high cost and imperfect on-site supporting construction equipment, it cannot be widely promoted and applied, and its general application has certain limitations.
[0004] Self-repairing material is an intelligent material that is pre-buried in the cement matrix. It can intelligently repair and fill the micro-cracks and micro-annular gaps in the cement annulus under a responsive environment, giving the cement annulus a self-repairing property, so that the cement annulus can realize intelligent response repair and long-term sealing integrity again. CN112391151A (Composition, self-repairing material and its preparation method and application for oil and gas well cementing) discloses a sulfonated styrene-butadiene block copolymer ionomer polymer material self-repairing agent, which gives the cement stone the ability to respond to and repair natural gas. CN111039586A (A self-repairing material used for oil and gas well cementing and its preparation method) discloses a new type of self-repairing material based on a core-shell structure, and the cement stone formed has the function of self-repairing cracks under high-pressure natural gas immersion conditions. CN111729660A (A self-repairing material for ultra-fine cracks in concrete and its preparation method), the nano-silica and water glass in the self-repairing material react with unhydrated cement particles and mineral admixtures to form calcium silicate gel, thereby realizing the self-repairing function of concrete cracks when they encounter water. Although the above self-healing materials give cement stone / concrete micro-cracks self-healing function, their response environment is high-pressure natural gas or water, that is, they are self-healing responsive materials when encountering hydrocarbons and water, and do not have the acidic medium CO2 response repair function. Summary of the invention
[0005] In order to solve the problems of annular air leakage and damage to wellbore integrity caused by micro-cracks and micro-annular gaps caused by cement annulus corrosion in injection and production wells under CCUS conditions, the purpose of the present invention is to provide a CO2 corrosion-resistant self-healing intelligent material and its preparation method and application. The CO2 corrosion-resistant self-healing intelligent material has a fast response speed in a CO2 environment, high responder strength, fast self-healing speed and good corrosion resistance.
[0006] In order to achieve the above-mentioned purpose, the present invention provides a CO2 corrosion resistant self-healing smart material, which has a core-shell structure; the core layer comprises a polymer obtained by polymerization of core layer monomers, and the core layer monomers include formaldehyde-urea prepolymer and crotonic acid; the shell layer comprises a polymer obtained by polymerization of shell layer monomers, and the shell layer monomers include acrylate monomers and cyclohexanelactam.
[0007] According to a specific embodiment of the present invention, preferably, based on the mass of the CO2 corrosion resistant self-healing smart material being 100%, the composition of the CO2 corrosion resistant self-healing smart material comprises 30-34% formaldehyde-urea prepolymer, 25-29% crotonic acid, 23-26% acrylate monomer, and 11-22% cyclohexanelactam.
[0008] According to a specific embodiment of the present invention, preferably, the acrylic acid ester monomer includes one or a combination of two or more of butyl acrylate, ethyl acrylate, methyl methacrylate, methyl acrylate, and isooctyl acrylate.
[0009] The present invention also provides a method for preparing the above-mentioned CO2 corrosion resistant self-repairing smart material, which comprises the following steps:
[0010] (1) emulsion polymerization of core layer monomers to obtain a core layer emulsion of the CO2 corrosion resistant self-healing smart material;
[0011] (2) The shell monomers are emulsion polymerized to prepare a shell layer on the surface of the core layer of the CO2 corrosion resistant self-healing smart material, thereby obtaining the CO2 corrosion resistant self-healing smart material.
[0012] According to a specific embodiment of the present invention, preferably, step (1) comprises the following steps:
[0013] (a) mixing the formaldehyde-urea prepolymer, crotonic acid, an emulsifier and water to obtain a core layer monomer solution;
[0014] (b) treating 25-35 wt % of the obtained core layer monomer solution with an initiator to obtain a core layer seed emulsion;
[0015] (c) adding the remaining core layer monomer solution and initiator to the obtained core layer seed emulsion for reaction to obtain the core layer emulsion of the CO2 corrosion resistant self-healing smart material.
[0016] According to a specific embodiment of the present invention, preferably, step (2) comprises the following steps:
[0017] (d) mixing the acrylic acid ester monomer, cyclohexanolactam, emulsifier and water to obtain a shell monomer solution;
[0018] (e) preparing a shell layer on the surface of the core layer of the CO2 corrosion resistant self-healing smart material by using the obtained shell layer monomer solution under the action of an initiator to obtain the CO2 corrosion resistant self-healing smart material.
[0019] According to a specific embodiment of the present invention, preferably, the preparation method of formaldehyde-urea prepolymer comprises the following steps: the raw material composition of formaldehyde-urea prepolymer comprises urea and formaldehyde in a molar ratio of 1:1.1-1:1.4; 35-42% of the total amount of urea raw material and polyacrylamide are mixed in water, the pH value is adjusted to 7-9 by triethanolamine, and the reaction is carried out at 50-65°C for 90-120min; then 40-50% of the total amount of urea raw material and formaldehyde solution (mass concentration is preferably 36%) are added, the pH value is adjusted to 4-6 by acetic acid, and the reaction is carried out for 120-150min; finally, 8-25% of the total amount of urea raw material is added, the pH value is adjusted to 4-6 by acetic acid, and the reaction is carried out at 65-70°C for 120-150min to obtain the formaldehyde-urea prepolymer; more preferably, the amount of polyacrylamide added is 3.5-6.2% of the total amount of urea raw material, and the molecular weight of the polyacrylamide is 3-5 million.
[0020] According to a specific embodiment of the present invention, preferably, the mass percentage concentration of the core layer monomer solution is 25-30% (calculated based on all solutes in the solution).
[0021] According to a specific embodiment of the present invention, preferably, in step (a), stirring is performed at 25000 r / min-28000 r / min for 15-20 min to obtain the core layer monomer solution.
[0022] According to a specific embodiment of the present invention, preferably, in step (a), the emulsifier includes a nonionic emulsifier, more preferably a mixture of dodecyl to octadecyl alcohol polyoxyethylene ether and octylphenol polyoxyethylene ether, further preferably a mixture of dodecyl to octadecyl alcohol polyoxyethylene ether and octylphenol polyoxyethylene ether in a mass ratio of 1:3.
[0023] According to a specific embodiment of the present invention, preferably, in step (a), the amount of the emulsifier added is 3.2-4.5% of the mass of the core layer monomer.
[0024] According to a specific embodiment of the present invention, preferably, in step (b), the amount of initiator added is 0.8-1.2% of the mass of the obtained core layer monomer solution of 25-35 wt%.
[0025] According to a specific embodiment of the present invention, preferably, in step (c), the amount of initiator added is 0.8-1.2% of the mass of the remaining core layer monomer solution.
[0026] According to a specific embodiment of the present invention, preferably, in step (b), the reaction temperature is 55-65°C.
[0027] According to a specific embodiment of the present invention, preferably, in step (c), at 65-70° C., the remaining core layer monomer solution and initiator are added dropwise to the core layer seed emulsion within 50-70 minutes, and the reaction is carried out for 6-8 hours.
[0028] According to a specific embodiment of the present invention, preferably, in step (b) or step (c), the initiator comprises azobisisobutyronitrile and ammonium persulfate, and more preferably, the initiator is added by configuring azobisisobutyronitrile and ammonium persulfate in a mass ratio of 1:1 into a composite solution with a mass concentration of 20-35% (calculated based on all solutes in the solution).
[0029] According to a specific embodiment of the present invention, preferably, the mass percentage concentration of the shell layer monomer solution is 20-25% (calculated based on all solutes in the solution).
[0030] According to a specific embodiment of the present invention, preferably, in step (d), stirring is performed at 25000 r / min-28000 r / min for 15-20 min to obtain the shell layer monomer solution.
[0031] According to a specific embodiment of the present invention, preferably, in step (e), the amount of initiator added is 0.8-1.0% of the mass of the shell layer monomer solution.
[0032] According to a specific embodiment of the present invention, preferably, in step (e), at 85-90° C., the shell layer monomer solution and initiator are added dropwise to the core layer emulsion within 120-140 min, and the reaction is carried out for 10-12 h.
[0033] According to a specific embodiment of the present invention, preferably, in step (d), the emulsifier includes one or a combination of two or more of nonylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate and sodium p-styrene sulfonate, more preferably a mixture of nonylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate and sodium p-styrene sulfonate in a mass ratio of 2:1:3.
[0034] According to a specific embodiment of the present invention, preferably, in step (d), the amount of the emulsifier added is 3.8-4.9% of the mass of the shell monomer.
[0035] According to a specific embodiment of the present invention, preferably, in step (e), the initiator comprises azobisisobutyronitrile and ammonium persulfate, and more preferably, the initiator is added in a composite solution of azobisisobutyronitrile and ammonium persulfate in a mass ratio of 1:1 and a mass concentration of 20-25% (calculated based on all solutes in the solution).
[0036] According to a specific embodiment of the present invention, the above preparation method comprises the following specific steps:
[0037] (1) Preparation of core layer CO2 responsive monomer solution:
[0038] Weigh formaldehyde-urea prepolymer, crotonic acid and emulsifier in proportion and dissolve them in water to prepare a solution with a mass percentage concentration of 25-30%, use a high-speed stirrer to mechanically stir the core layer monomer mixture for 15-20 minutes to obtain a core layer CO2 responsive monomer solution, and the stirring speed is 25000r / min-28000r / min;
[0039] The specific synthesis steps of the formaldehyde-urea prepolymer are as follows: the molar ratio of urea to formaldehyde is controlled to be 1:1.1-1:1.4. Weigh 35-42% of the total amount of urea and polyacrylamide and dissolve them in water, adjust the pH value of the system to 7-9 with triethanolamine, heat to 50-65°C and stir to react for 90-120 minutes; then add the remaining 40-50% urea and a formaldehyde solution with a specified mass concentration of 36%, adjust the pH value of the system to 4-6 with acetic acid solution, and stir to react for 120-150 minutes; finally weigh 8-25% of the total amount of urea, adjust the pH value to 4-6 with acetic acid solution, heat to 65-70°C and stir to react for 120-150 minutes to obtain the formaldehyde-urea prepolymer. The amount of polyacrylamide added is 3.5-6.2% of the total amount of urea, and its molecular weight is 3-5 million;
[0040] (2) Preparation of shell temperature responsive softening functional monomer solution:
[0041] Weighing acrylate monomers, cyclohexanolactam and emulsifiers in proportion and dissolving them in water to prepare a solution with a mass percentage concentration of 20-25%, using a high-speed stirrer to mechanically stir the shell monomer mixture for 15-20 minutes to obtain a shell temperature-responsive softening functional monomer solution, and the stirring speed is 25000r / min-28000r / min;
[0042] (3) Preparation of nuclear layer seed emulsion:
[0043] Weigh one-fourth of the core layer CO2 responsive monomer solution prepared in step (1) and add it to a five-necked flask equipped with a condenser, a stirrer, and a thermometer, heat it to 55-65°C in a water bath and keep it at this temperature for 30 minutes, add 0.8-1.2% of the initiator by weight of one-fourth of the core layer CO2 responsive monomer solution, and wait until the solution shows a slight blue glow and the reflux disappears, thus obtaining the core layer seed emulsion;
[0044] (4) Preparation of core layer of CO2 corrosion resistant self-healing material:
[0045] Weigh the remaining three quarters of the core layer CO2 responsive monomer solution in step (1) and 0.8-1.2% of the total mass of the three quarters of the monomer solution initiator, place them in constant pressure dropping funnel A and constant pressure dropping funnel B respectively, and install them on the five-necked flask in step (3), introduce nitrogen to deoxygenate for 15 minutes, heat the water bath to 65-70°C and keep the temperature constant for 30 minutes, open the constant pressure dropping funnel A and the constant pressure dropping funnel B, control the addition to be completed within 50-70 minutes, and continue the reaction for 6.0-8.0 hours, thus completing the preparation of the core layer of the CO2 corrosion resistant self-healing material;
[0046] (5) Preparation of CO2 corrosion resistant self-healing material shell:
[0047] The shell temperature responsive softening functional monomer solution in step (2) and 0.8-1.0% of the total mass of the initiator are placed in constant pressure dropping funnel C and constant pressure dropping funnel D respectively, and installed on the five-necked flask in step (4), and the water bath is heated to 80-90°C and kept at this temperature for 30 minutes. The constant pressure dropping funnel C and the constant pressure dropping funnel D are opened, and the reaction is continued for 10.0-12.0 hours after the addition is completed at 120-140 minutes. After cooling to room temperature, a CO2 corrosion-resistant self-healing smart material is obtained.
[0048] The present invention also provides the application of the above-mentioned CO2 corrosion resistant self-repairing intelligent material in oil well cement.
[0049] The CO2 corrosion resistant self-healing intelligent material of the present invention is a "hard core and soft shell" microsphere form. Due to the soft shell characteristics, the material is endowed with deformation characteristics. On the one hand, it can form a particle grading with cement particles to increase the density of the cement matrix. On the other hand, since it is filled in the pores of cement stone, it can form a polymer barrier under the action of pressure difference and water loss process, which has an anti-corrosion effect. At the same time, the core layer contains a large number of -OH and -COOH response groups, which give the material CO2 response repair characteristics. The introduced crotonic acid not only makes the core-shell interface better fused, but the hydrophilic group -COOH contained in it also has acidic response characteristics.
[0050] The present invention is based on the hydroxyl condensation theory. By introducing CO2 responsive functional monomers with hydroxyl / carboxyl groups, the self-healing material is endowed with CO2 responsive function, high filling material strength, and strong repair continuity. On the other hand, by introducing softening functional monomers with temperature responsive characteristics, the present invention endows the self-healing material with softening characteristics, and achieves the purpose of improving the CO2 corrosion resistance of the cement sheath through the polymer barrier effect. The invention has a fast response speed, high responder strength, fast self-repair speed, and good corrosion resistance in the CO2 environment under CCUS working conditions. It can respond to and repair CO2 in acidic media, realize self-repair and reshape the seal of the annular cement ring, and ensure safe CO2 storage and efficient oil recovery efficiency. The present invention has the following significant advantages:
[0051] 1. The CO2 corrosion resistant self-repairing smart material of the present invention is a core-shell structure polymer microsphere with a particle size distribution in the nanometer range. It can easily form a good particle grading effect and a tight stacking effect with cement clinker, improve the suspension stability of cement slurry and the density of cement stone matrix, and give cement stone good impermeability;
[0052] 2. The CO2 corrosion resistant self-repairing smart material of the present invention has good CO2 response characteristics. It has rapid acidic medium response characteristics in a CO2 environment, forming a high-strength three-dimensional solidified material with good compressive strength and repair strength;
[0053] 3. The CO2 corrosion resistant self-repairing smart material of the present invention has good softening properties and toughness. It has a fast temperature response characteristic under normal temperature environment and can form a polymer material with a continuous distribution state with full toughness;
[0054] 4. The CO2 corrosion resistant self-healing smart material of the present invention has good CO2 corrosion resistance and self-healing properties. Compared with conventional cement stone and other self-healing agent products on the market, the cement stone formed by this product, under the conditions of total pressure of 35MPa\CO2 partial pressure of 30MPa, after 90 days of CO2 corrosion curing, the compressive strength stability can be enhanced by 91.00%, and the permeability recovery rate can be enhanced by 88.00%. DETAILED DESCRIPTION
[0055] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0056] Preparation Example 1
[0057] This preparation example provides a formaldehyde-urea prepolymer, which is prepared by the following steps:
[0058] The molar ratio of urea to formaldehyde is controlled to be 1:1.2. Weigh 55.5g of urea and 6.0g of polyacrylamide with a molecular weight of 5 million and dissolve them in 100g of water. Use triethanolamine to adjust the pH value to 7, transfer to a 500mL three-necked flask, start the stirrer and heat to 55°C for stirring and reaction for 100min; then add 60g of urea and 249.75g of 36% mass concentration formaldehyde solution, use acetic acid solution to adjust the pH value of the system to 4, stir and react for 120min; finally, add 34.5g of urea, use acetic acid solution to adjust the pH value to 4, heat to 65°C and stir and react for 130min to obtain formaldehyde-urea prepolymer.
[0059] Preparation Example 2
[0060] This preparation example provides a formaldehyde-urea prepolymer comparative sample, which is prepared by the following steps:
[0061] The molar ratio of urea to formaldehyde is controlled to be 1:1.2. Weigh 55.5g of urea and 6.0g of polyacrylamide with a molecular weight of 5 million and dissolve them in 100g of water. Use sodium hydroxide to adjust the pH value to 7, transfer to a 500mL three-necked flask, start the stirrer and heat to 55°C for stirring and reaction for 100min; then add 60g of urea and 249.75g of 36% mass concentration formaldehyde solution, use acetic acid solution to adjust the system pH value to 4, stir and react for 120min; finally, add 34.5g of urea, use acetic acid solution to adjust the pH value to 4, heat to 65°C and stir and react for 130min to obtain a formaldehyde-urea prepolymer comparison sample. After the comparison sample is discharged, it is allowed to stand for 3.0 hours and directly stratified, and cannot be directly used later.
[0062] Example 1
[0063] This embodiment provides a CO2 corrosion resistant self-repairing smart material, which is prepared by the following steps:
[0064] (1) Preparation of core layer CO2 responsive monomer solution:
[0065] Weigh 30 g of formaldehyde-urea prepolymer (the product obtained in Preparation Example 1, the same below), 25 g of crotonic acid, 0.44 g of dodecyl alcohol polyoxyethylene ether, and 1.32 g of octylphenol polyoxyethylene ether and dissolve them in 165 g of water, adjust the stirrer speed to 26000 r / min, and stir the mixture at high speed for 15 min to obtain a core layer CO2 responsive monomer solution;
[0066] (2) Preparation of shell temperature responsive softening functional monomer solution:
[0067] Weigh 23 g of methyl methacrylate, 22 g of cyclohexane lactam, 0.70 g of nonylphenol polyoxyethylene ether, 0.35 g of sodium dodecylbenzene sulfonate, and 1.04 g of sodium p-styrene sulfonate and dissolve them in 220 g of water. Adjust the stirrer speed to 26000 r / min and stir the mixture at high speed for 15 min to obtain a shell temperature responsive softening functional monomer solution.
[0068] (3) Preparation of nuclear layer seed emulsion:
[0069] Weigh 55.44 g of the core layer CO2 responsive monomer solution and add it to a five-necked flask equipped with a condenser, a stirrer, and a thermometer. Heat the water bath to 55°C and keep the temperature constant for 30 min. Add 2.22 g of azobisisobutyronitrile and ammonium persulfate compound (mass ratio is 1:1) initiator solution (mass concentration is 20%). When the solution shows a slight blue glow and the reflux disappears, the core layer seed emulsion is obtained.
[0070] (4) Preparation of core layer of CO2 corrosion resistant self-healing material:
[0071] Weigh 166.32g of the core layer CO2 responsive monomer solution and 6.65g of the initiator solution (mass concentration of 20%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1), place them in constant pressure dropping funnel A and constant pressure dropping funnel B respectively, and install them on the five-necked flask in step (3), introduce nitrogen to deoxygenate for 15min, heat the water bath to 65°C and keep the temperature constant for 30min, open constant pressure dropping funnel A and constant pressure dropping funnel B, control the addition to be completed within 50min, and continue the reaction for 6.0h, thus completing the preparation of the core layer of the CO2 corrosion resistant self-healing material;
[0072] (5) Preparation of CO2 corrosion resistant self-healing material shell:
[0073] Weigh 267.09g of shell temperature responsive softening functional monomer solution and 6.65g of azobisisobutyronitrile and ammonium persulfate composite initiator (mass ratio of 1:1) solution (mass concentration of 20%) and place them in constant pressure dropping funnel C and constant pressure dropping funnel D respectively and install them on the five-necked flask in step (4). Heat the water bath to 90°C and keep the temperature constant for 30min. Open the constant pressure dropping funnel C and the constant pressure dropping funnel D. After the addition is completed within 120min, continue the reaction for 12.0h. After cooling to room temperature, the CO2 corrosion resistant self-healing smart material A is obtained.
[0074] Example 2
[0075] This embodiment provides a CO2 corrosion resistant self-repairing smart material, which is prepared by the following steps:
[0076] (1) Preparation of core layer CO2 responsive monomer solution:
[0077] Weigh 34 g of formaldehyde-urea prepolymer, 29 g of crotonic acid, 0.71 g of tridecaned fatty alcohol polyoxyethylene ether, and 2.13 g of octylphenol polyoxyethylene ether and dissolve them in 147 g of water. Adjust the stirrer speed to 28000 r / min and stir the mixture at high speed for 20 min to obtain a core layer CO2 responsive monomer solution.
[0078] (2) Preparation of shell temperature responsive softening functional monomer solution:
[0079] Weigh 26 g of methyl methacrylate, 11 g of cyclohexane lactam, 0.60 g of nonylphenol polyoxyethylene ether, 0.30 g of sodium dodecylbenzene sulfonate, and 0.90 g of sodium p-styrene sulfonate and dissolve them in 111 g of water. Adjust the stirrer speed to 28000 r / min and stir the mixture at high speed for 15 min to obtain a shell temperature responsive softening functional monomer solution.
[0080] (3) Preparation of nuclear layer seed emulsion:
[0081] Weigh 53.21g of the core layer CO2 responsive monomer solution and add it to a five-necked flask equipped with a condenser, a stirrer, and a thermometer. Heat it to 60°C in a water bath and keep it at this temperature for 30min. Add 2.13g of an initiator solution (mass concentration of 22%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1). When the solution shows a slight blue glow and the reflux disappears, the core layer seed emulsion is obtained.
[0082] (4) Preparation of core layer of CO2 corrosion resistant self-healing material:
[0083] Weigh 159.63 g of the core layer CO2 responsive monomer solution and 6.39 g of azobisisobutyronitrile and ammonium persulfate compound (mass ratio of 1:1) initiator solution (mass concentration of 22%), place them in constant pressure dropping funnel A and constant pressure dropping funnel B respectively, and install them on the five-necked flask in step (3), pass nitrogen to deoxygenate for 15 min, heat the water bath to 65°C and keep the temperature constant for 30 min, open the constant pressure dropping funnel A and the constant pressure dropping funnel B, control the addition to be completed within 60 min, and continue the reaction for 7.0 h, thus completing the preparation of the core layer of the CO2 corrosion resistant self-healing material;
[0084] (5) Preparation of CO2 corrosion resistant self-healing material shell:
[0085] Weigh 111.0 g of shell temperature responsive softening functional monomer solution and 4.44 g of azobisisobutyronitrile and ammonium persulfate composite (mass ratio of 1:1) initiator solution (mass concentration of 22%) and place them in constant pressure dropping funnel C and constant pressure dropping funnel D respectively and install them on the five-necked flask in step (4). Heat the water bath to 85°C and keep the temperature constant for 30 min. Open the constant pressure dropping funnel C and the constant pressure dropping funnel D. After the addition is completed within 130 min, continue the reaction for 11.0 h. After cooling to room temperature, the CO2 corrosion resistant self-healing smart material B is obtained.
[0086] Comparative Example 1
[0087] This comparative example provides a comparative sample of a CO2 corrosion resistant self-repairing material, which is prepared by the following steps:
[0088] (1) Preparation of core layer CO2 responsive monomer solution:
[0089] Weigh 30 g of formaldehyde-urea prepolymer (the product obtained in Preparation Example 1, the same below), 25 g of acrylic acid, 0.44 g of dodecyl alcohol polyoxyethylene ether, and 1.32 g of octylphenol polyoxyethylene ether and dissolve them in 165 g of water, adjust the stirrer speed to 26000 r / min, and stir the mixture at high speed for 15 min to obtain a core layer CO2 responsive monomer solution;
[0090] (2) Preparation of shell temperature responsive softening functional monomer solution:
[0091] Weigh 23 g of methyl methacrylate, 22 g of cyclohexane lactam, 0.70 g of nonylphenol polyoxyethylene ether, 0.35 g of sodium dodecylbenzene sulfonate, and 1.04 g of sodium p-styrene sulfonate and dissolve them in 220 g of water. Adjust the stirrer speed to 26000 r / min and stir the mixture at high speed for 15 min to obtain a shell temperature responsive softening functional monomer solution.
[0092] (3) Preparation of nuclear layer seed emulsion:
[0093] Weigh 55.44 g of the core layer CO2 responsive monomer solution and add it to a five-necked flask equipped with a condenser, a stirrer, and a thermometer. Heat the water bath to 55°C and keep the temperature constant for 30 min. Add 2.22 g of azobisisobutyronitrile and ammonium persulfate compound (mass ratio is 1:1) initiator solution (mass concentration is 20%). When the solution shows a slight blue glow and the reflux disappears, the core layer seed emulsion is obtained.
[0094] (4) Preparation of core layer of CO2 corrosion resistant self-healing material:
[0095] Weigh 166.32g of the core layer CO2 responsive monomer solution and 6.65g of the initiator solution (mass concentration of 20%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1), place them in constant pressure dropping funnel A and constant pressure dropping funnel B respectively, and install them on the five-necked flask in step (3), introduce nitrogen to deoxygenate for 15min, heat the water bath to 65°C and keep the temperature constant for 30min, open constant pressure dropping funnel A and constant pressure dropping funnel B, control the addition to be completed within 50min, and continue the reaction for 6.0h, thus completing the preparation of the core layer of the CO2 corrosion resistant self-healing material;
[0096] (5) Preparation of CO2 corrosion resistant self-healing material shell:
[0097] Weigh 267.09g of shell temperature responsive softening functional monomer solution and 6.65g of azobisisobutyronitrile and ammonium persulfate composite initiator (mass ratio of 1:1) solution (mass concentration of 20%) and place them in constant pressure dropping funnel C and constant pressure dropping funnel D respectively and install them on the five-necked flask in step (4), heat the water bath to 90°C and keep the temperature constant for 30min, open the constant pressure dropping funnel C and the constant pressure dropping funnel D, control the addition to be completed within 120min, and continue the reaction for 12.0h. After cooling to room temperature, a comparison sample C of the CO2 corrosion resistant self-healing material is obtained.
[0098] Comparative Example 2
[0099] This comparative example provides a comparative sample of a CO2 corrosion resistant self-repairing material, which is prepared by the following steps:
[0100] (1) Preparation of core layer CO2 responsive monomer solution:
[0101] Weigh 34 g of formaldehyde-urea prepolymer, 29 g of crotonic acid, 0.91 g of heptathalloyl polyoxyethylene ether, and 0.91 g of octylphenol polyoxyethylene ether and dissolve them in 147 g of water. Adjust the stirrer speed to 28000 r / min and stir the mixture at high speed for 20 min to obtain a core layer CO2 responsive monomer solution.
[0102] (2) Preparation of shell temperature responsive softening functional monomer solution:
[0103] Weigh 26 g of methyl methacrylate, 11 g of cyclohexanolactam, 0.43 g of octylphenol polyoxyethylene ether, 0.43 g of sodium dodecyl sulfate, and 0.43 g of sodium p-styrene sulfonate and dissolve them in 111 g of water. Adjust the stirrer speed to 28000 r / min and stir the mixture at high speed for 15 min to obtain a shell temperature responsive softening functional monomer solution.
[0104] (3) Preparation of nuclear layer seed emulsion:
[0105] Weigh 53.21g of the core layer CO2 responsive monomer solution and add it to a five-necked flask equipped with a condenser, a stirrer, and a thermometer. Heat it to 60°C in a water bath and keep it at this temperature for 30min. Add 2.13g of an initiator solution (mass concentration of 22%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1). When the solution shows a slight blue glow and the reflux disappears, the core layer seed emulsion is obtained.
[0106] (4) Preparation of core layer of CO2 corrosion resistant self-healing material:
[0107] Weigh 159.63 g of the core layer CO2 responsive monomer solution and 6.39 g of azobisisobutyronitrile and ammonium persulfate compound (mass ratio of 1:1) initiator solution (mass concentration of 22%), place them in constant pressure dropping funnel A and constant pressure dropping funnel B respectively, and install them on the five-necked flask in step (3), pass nitrogen to deoxygenate for 15 min, heat the water bath to 65°C and keep the temperature constant for 30 min, open the constant pressure dropping funnel A and the constant pressure dropping funnel B, control the addition to be completed within 60 min, and continue the reaction for 7.0 h, thus completing the preparation of the core layer of the CO2 corrosion resistant self-healing material;
[0108] (5) Preparation of CO2 corrosion resistant self-healing material shell:
[0109] Weigh 111.0g of shell temperature responsive softening functional monomer solution and 4.44g of azobisisobutyronitrile and ammonium persulfate compound (mass ratio of 1:1) initiator solution (mass concentration of 22%) and place them in constant pressure dropping funnel C and constant pressure dropping funnel D respectively and install them on the five-necked flask in step (4), heat the water bath to 85°C and keep the temperature constant for 30min, open constant pressure dropping funnel C and constant pressure dropping funnel D, control the addition to be completed within 130min, continue the reaction for 11.0h, and cool to room temperature to obtain CO2 corrosion resistant self-healing material comparison sample D. This sample has poor stability and is directly stratified, so it cannot be directly applied to cement slurry, and there is no need to test its CO2 corrosion resistance and self-healing properties.
[0110] Comparative Example 3
[0111] This comparative example provides a comparative sample of a CO2 corrosion resistant self-repairing material, which is prepared by the following steps:
[0112] (1) Preparation of core layer CO2 responsive monomer solution:
[0113] Weigh 34 g of formaldehyde-urea prepolymer, 29 g of crotonic acid, 0.71 g of tridecaned fatty alcohol polyoxyethylene ether, and 2.13 g of octylphenol polyoxyethylene ether and dissolve them in 147 g of water. Adjust the stirrer speed to 21000 r / min and stir the mixture at high speed for 20 min to obtain a core layer CO2 responsive monomer solution.
[0114] (2) Preparation of shell temperature responsive softening functional monomer solution:
[0115] Weigh 26 g of methyl methacrylate, 11 g of cyclohexane lactam, 0.60 g of nonylphenol polyoxyethylene ether, 0.30 g of sodium dodecylbenzene sulfonate, and 0.90 g of sodium p-styrene sulfonate and dissolve them in 111 g of water. Adjust the stirrer speed to 21000 r / min and stir the mixture at high speed for 15 min to obtain a shell temperature responsive softening functional monomer solution.
[0116] (3) Preparation of nuclear layer seed emulsion:
[0117] Weigh 53.21g of the core layer CO2 responsive monomer solution and add it to a five-necked flask equipped with a condenser, a stirrer, and a thermometer. Heat it to 60°C in a water bath and keep it at this temperature for 30min. Add 2.13g of an initiator solution (mass concentration of 22%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1). When the solution shows a slight blue glow and the reflux disappears, the core layer seed emulsion is obtained.
[0118] (4) Preparation of core layer of CO2 corrosion resistant self-healing material:
[0119] Weigh 159.63 g of the core layer CO2 responsive monomer solution and 6.39 g of azobisisobutyronitrile and ammonium persulfate compound (mass ratio of 1:1) initiator solution (mass concentration of 22%), place them in constant pressure dropping funnel A and constant pressure dropping funnel B respectively, and install them on the five-necked flask in step (3), pass nitrogen to deoxygenate for 15 min, heat the water bath to 65°C and keep the temperature constant for 30 min, open the constant pressure dropping funnel A and the constant pressure dropping funnel B, control the addition to be completed within 60 min, and continue the reaction for 7.0 h, thus completing the preparation of the core layer of the CO2 corrosion resistant self-healing material;
[0120] (5) Preparation of CO2 corrosion resistant self-healing material shell:
[0121] Weigh 111.0g of shell temperature responsive softening functional monomer solution and 4.44g of azobisisobutyronitrile and ammonium persulfate compound (mass ratio of 1:1) initiator solution (mass concentration of 22%) and place them in constant pressure dropping funnel C and constant pressure dropping funnel D respectively and install them on the five-necked flask in step (4), heat the water bath to 85°C and keep the temperature constant for 30min, open constant pressure dropping funnel C and constant pressure dropping funnel D, control the addition to be completed within 130min, and continue the reaction for 11.0h, and cool to room temperature to obtain CO2 corrosion resistant self-healing material comparison sample E. After the sample was discharged and left to stand for 2 hours, it was directly stratified, which made it impossible to directly apply it to cement slurry, so there was no need to test its CO2 corrosion resistance and self-healing performance.
[0122] Test Example 1
[0123] The CO2 corrosion resistant self-healing intelligent materials and the control samples prepared in Example 1, Example 2 and Comparative Example 1 were added to the conventional density oil well cement system to form cement stones A, B and C respectively, and placed in a high temperature and high pressure curing kettle. Under the conditions of 90°C, total pressure of 35MPa and CO2 partial pressure of 30MPa, after continuous curing for 90 days, the compressive strength stability and the fracture permeability recovery rate were shown in Table 1, and the test was carried out according to the oil well cement test method GB / T 19139-2012.
[0124] Table 1. Compressive strength stabilizer and permeability recovery of cement paste prepared by self-repairing intelligent materials against CO2 corrosion
[0125]
[0126] In Table 1, the blank cement system formula is: G-grade oil well cement + 0.2% dispersant (G408FJ) + 0.44% tap water, density 1.90g / cm 3 ;
[0127] A or B or C cement system formula: G-grade oil well cement + 0.2% dispersant (G408FJ) + 6% anti-CO2 corrosion self-repairing smart material (or comparison sample C) + 0.44% tap water, density 1.90g / cm 3 .
[0128] The experimental results show that: under the conditions of 90℃\total pressure of 35MPa\CO2 partial pressure of 30MPa, after continuous curing for 90 days, the compressive strength decline rates of blank cement paste, cement paste A, cement paste B and cement paste C were 69.41%, 6.25%, 4.11% and 45.33%, respectively. Compared with blank cement paste, the compressive strength stability of cement paste A, cement paste B and cement paste C were enhanced by 91.00%, 94.08% and 34.69%, respectively; the permeability recovery rates of blank cement paste, cement paste A, cement paste B and cement paste C were 12.14%, 88.00%, 90.07% and 24.12%, respectively. Compared with blank cement paste, the permeability recovery rates of cement paste A, cement paste B and cement paste C were enhanced by 75.86%, 77.93% and 11.98%, respectively. Therefore, the cement stone prepared by the present invention has good corrosion resistance and CO2 response self-repairing performance, and can solve the technical problems of cement ring matrix destruction caused by acidic medium CO2 corrosion of the wellbore cementing ring of the injection and production well in CCUS project construction, annular air leakage caused by micro-gaps and micro-cracks in the annulus, and damage to the wellbore integrity.
Claims
1. A CO2 corrosion resistant self-healing smart material having a core-shell structure; the core layer comprises a polymer obtained by polymerization of core layer monomers, the core layer monomers include formaldehyde-urea prepolymer and crotonic acid; the shell layer comprises a polymer obtained by polymerization of shell layer monomers, the shell layer monomers include acrylate monomers and cyclohexanolactam.
2. The CO2 corrosion resistant self-repairing smart material according to claim 1, wherein: Taking the mass of the CO2 corrosion resistant self-repairing smart material as 100%, the composition of the CO2 corrosion resistant self-repairing smart material comprises 30-34% formaldehyde-urea prepolymer, 25-29% crotonic acid, 23-26% acrylate monomer, and 11-22% cyclohexanolactam; Preferably, the acrylic acid ester monomer includes one or a combination of two or more of butyl acrylate, ethyl acrylate, methyl methacrylate, methyl acrylate, and isooctyl acrylate.
3. The method for preparing the CO2 corrosion resistant self-repairing smart material according to claim 1 or 2, comprising the following steps: (1) emulsion polymerization of core layer monomers to obtain a core layer emulsion of the CO2 corrosion resistant self-healing smart material; (2) The shell monomers are emulsion polymerized to prepare a shell layer on the surface of the core layer of the CO2 corrosion resistant self-healing smart material, thereby obtaining the CO2 corrosion resistant self-healing smart material.
4. The preparation method according to claim 3, wherein Step (1) comprises the following steps: (a) mixing the formaldehyde-urea prepolymer, crotonic acid, an emulsifier and water to obtain a core layer monomer solution; (b) treating 25-35 wt % of the obtained core layer monomer solution with an initiator to obtain a core layer seed emulsion; (c) adding the remaining core layer monomer solution and initiator to the obtained core layer seed emulsion for reaction to obtain the core layer emulsion of the CO2 corrosion resistant self-healing smart material.
5. The preparation method according to claim 3, wherein: Step (2) comprises the following steps: (d) mixing the acrylic acid ester monomer, cyclohexanolactam, emulsifier and water to obtain a shell monomer solution; (e) preparing a shell layer on the surface of the core layer of the CO2 corrosion resistant self-healing smart material by using the obtained shell layer monomer solution under the action of an initiator to obtain the CO2 corrosion resistant self-healing smart material.
6. The preparation method according to claim 3, wherein: The preparation method of formaldehyde-urea prepolymer comprises the following steps: The raw material composition of the formaldehyde-urea prepolymer includes urea and formaldehyde in a molar ratio of 1:1.1-1:1.4; 35-42% of the total amount of urea raw materials and polyacrylamide are mixed in water, the pH value is adjusted to 7-9 by triethanolamine, and the mixture is reacted at 50-65° C. for 90-120 minutes; 40-50% of the total amount of urea raw materials and formaldehyde solution are then added, the pH value is adjusted to 4-6 by acetic acid, and the mixture is reacted for 120-150 minutes; finally, 8-25% of the total amount of urea raw materials are added, the pH value is adjusted to 4-6 by acetic acid, and the mixture is reacted at 65-70° C. for 120-150 minutes to obtain the formaldehyde-urea prepolymer; Preferably, the amount of polyacrylamide added is 3.5-6.2% of the total amount of urea raw material, and the molecular weight of the polyacrylamide is 3-5 million.
7. The preparation method according to claim 4, wherein The mass percentage concentration of the core layer monomer solution is 25-30%; Preferably, in step (a), stirring is performed at 25000 r / min-28000 r / min for 15-20 min to obtain the core layer monomer solution; Preferably, in step (a), the emulsifier comprises a nonionic emulsifier, more preferably a mixture of dodecyl to octadecyl alcohol polyoxyethylene ether and octylphenol polyoxyethylene ether, further preferably a mixture of dodecyl to octadecyl alcohol polyoxyethylene ether and octylphenol polyoxyethylene ether in a mass ratio of 1:3; Preferably, in step (a), the amount of the emulsifier added is 3.2-4.5% of the mass of the core layer monomer; Preferably, in step (b), the amount of initiator added is 0.8-1.2% of the mass of the obtained core layer monomer solution of 25-35wt%; Preferably, in step (c), the amount of initiator added is 0.8-1.2% of the mass of the remaining core layer monomer solution; Preferably, in step (b), the reaction temperature is 55-65°C; Preferably, in step (c), the remaining core layer monomer solution and initiator are added dropwise to the core layer seed emulsion at 65-70° C. for 50-70 min, and the reaction is carried out for 6-8 h; Preferably, in step (b) or step (c), the initiator comprises azobisisobutyronitrile and ammonium persulfate. More preferably, the initiator is added in the form of a composite solution of azobisisobutyronitrile and ammonium persulfate in a mass ratio of 1:1 with a mass concentration of 20-35%.
8. The preparation method according to claim 5, wherein The mass percentage concentration of the shell monomer solution is 20-25%; Preferably, in step (d), stirring is performed at 25000 r / min-28000 r / min for 15-20 min to obtain the shell monomer solution; Preferably, in step (e), the amount of initiator added is 0.8-1.0% of the mass of the shell monomer solution; Preferably, in step (e), the shell layer monomer solution and the initiator are added dropwise to the core layer emulsion at 85-90° C. for 120-140 min, and the reaction is continued for 10-12 h; Preferably, in step (d), the emulsifier comprises nonylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate and sodium p-styrene sulfonate, more preferably a mixture of nonylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate and sodium p-styrene sulfonate in a mass ratio of 2:1:3; Preferably, in step (d), the amount of the emulsifier added is 3.8-4.9% of the mass of the shell monomer; Preferably, in step (e), the initiator comprises azobisisobutyronitrile and ammonium persulfate, and more preferably, the initiator is added in the form of a composite solution of azobisisobutyronitrile and ammonium persulfate in a mass ratio of 1:1 with a mass concentration of 20-25%.
9. Application of the CO2 corrosion resistant self-repairing intelligent material according to claim 1 or 2 in oil well cement.
Citation Information
Patent Citations
Self-repairing material for oil and gas well cementation and preparation method
CN111039586A
Magnetic nano material with CO2 responsiveness as well as preparation method and application thereof
CN111729660A
Composition for oil-gas well cementation, self-repairing material, preparation method and application of self-repairing material
CN112391151A